The Effectiveness of Fall Prevention Program for the Older Adults in Urban Communities, Udon Thani Province - Moongsamak, Nannaphas; Sriboonpimsuay, Wanlapa (Journal of The Royal Thai Army Nurses, 2026)
Falls are a major cause of injury that causes the older adults to be hospitalized, which affects their quality of life. Therefore, fall prevention for the older adults is an important to reduce this problem. The purpose of this research was to study the effectiveness of a fall prevention program for the older adults in an urban community in Udon Thani Province. Quasi-experimental study two group pre-post Test design, they were divided into experimental and control groups, with 50 subjects in each group, participants were selected by purposive sampling, duration 16 weeks. The instruments were divided into 2 parts: 1) a questionnaire for collecting data consisting of (1) personal information, (2) knowledge on fall prevention, (3) behavior to prevent falls, (4) balance assessment form, (5) fear of falling, and 2) a fall prevention program for the elderly. Descriptive statistics, and t-test were used to analyze data. The results revealed that the knowledge, behavior, and balance scores were significantly higher than before receiving the program and higher than the control group (p<.05). The fear scores were significantly lower than before receiving the program and lower than the control group (p<.05). Therefore, healthcare professionals can apply this program to encourage awareness of risks, strengthen fall prevention behavior, and increase balance ability to reduce the risk of falls in the older adults.